Peran Program Kelas Khusus Keagamaan dalam Membentuk Karakter Religius Peserta Didik di SMPN 2 Mojokerto - Dwi Mariatul Qibtia; Muhammad Fahmi; Fathur Rohman (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to determine the role of the special religious class program in shaping the religious character of students at SMPN 2 Mojokerto. The background of this research is driven by the increasing need for character education to answer the challenges of modern times. This research uses a qualitative approach with a case study method with a focus on the implementation of the religious class program at school. Data collection techniques include interviews, observation, and documentation. The research findings show that the religious class program has a positive effect on the development of students' religious character, especially through activities such as memorizing the Quran, regular religious studies, and guidance from religious teachers. The program not only improves students' understanding of Islamic teachings but also fosters discipline, responsibility, and ethical behavior in daily life. In addition, the role of teachers is crucial in ensuring the success of the program by providing direct guidance and serving as role models for students.